AN EXPLORATORY STUDY ON SOCIAL LEARNING THEORY, SOCIAL BOND THEORY, EXPERIENCES WITH POLICE AND DEMOGRAPHIC EFFECTS ON COLLEGE STUDENT ATTITUDES TOWARD POLICE - McLean, Tyson Allen (2012)
Research on public attitudes toward police is principally conducted through survey methods focused on analyzing the effects of experiences with police, satisfaction with police services and respondent demographics. Most research collects data from the general public, which overall reports high levels of satisfaction with the police. However, few studies focus on the college student population and fewer integrate theoretical frameworks to explore this complex issue. This research incorporates tenets from social learning and social control theories as a conceptual framework from which the analysis is built. It also explores the role that personal and vicarious contact and demographic influences play in variations among college student attitudes toward police. To collect data for this study an internet-based survey instrument was sent electronically to every part-time and full-time student at The University of Montana attending classes in the fall 2011 semester. Questions asked respondents to report on their attitudes toward police, orientation toward crime and alcohol use, direct and vicarious experiences with police, as well as, items derived from empirically validated social learning and social bond concepts. Similar questions pertaining to the individual’s understanding of their friends and family experiences with police and criminal orientations were also included. Ordinary least squares regression is used to evaluate social learning, social bond, vicarious and direct experiences with police and demographic variable’s abilities to predict variations in college student attitudes toward police. The study’s results show that social learning and social bond derived variables, as well as, vicarious and direct experiences with police explain more of the variation in attitudes towards police than demographic variables. The social learning model explains the most variation in attitudes toward police compared to all the other stand-alone models. A complete model that incorporates all the variables provides the most robust prediction for the variation in attitudes toward police. A discussion of the limitations of the current study and recommendations for future research is also provided